Vampire kisses - Schreiber, Ellen (Vampire Kisses, 2003)
Sixteen-year-old Raven, an outcast who always wears black and hopes to become a vampire some day, falls in love with the mysterious new boy in town, eager to find out if he can make her dreams come true.